KEMAMPUAN SERAPAN ABU TULANG SAPI TERHADAP VARIASI KONSENTRASI ION NITRAT - Yusnita, N.; Anita, S.; ', Itnawita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cow bone ash is one of some alternative adsorbents, since it contains many oxide compoundssuch as calcium oxide that has an open framework structure. The aim of this study was todetermine the adsorption ability of the cow bone ash on nitrate ion based of the concentrationvariation. Nitrate analysis was carried out using UV-VIS spectrophotometer with brucine-sulfate method. The results showed that concentration affected the adsorption of cow bone ashon nitrate ion with optimum adsorption ability (80.050%) at 10 mg/L.